(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
There are various minor ailments occur during pregnancy, where nausea and vomiting are usually common in early pregnancy. Vomiting in early weeks of pregnancy, mentioned as Garbhini Chardi (Emesis Graviderum) in Vyakt Garbha Lakshana in classics. If this vomiting is not corrected at right time, it may cause many complications later. Due to sedentary lifestyle, changed food habits, stress etc. has made pregnancies more difficult in today’s era. Modern obstetrics practice manages emesis gravidarum using drugs like anti-emetics, antacids, giving nutritional support with vitamin B1, B6, B12. Moreover, drugs like anti-emetics etc. subsides the symptoms but they are having some minimal side effects too such as constipation, dysuria, urinary retention etc. So, Ayurveda approach is found to be very useful in such condition, many formulations are mentioned in our classics which can be incorporated in daily life by pregnant woman. Acharya Yogaratnakar in Streeroga Chikitsa have mentioned many herbal formulations for garbhini Chardi. Here, Sunthi Bilwa Kwath with Yava Saktu formulation may subsides the vomiting during pregnancy due to Kasaya Ras and Ruksha Guna of Bilwa and Yava Saktu, Deepan, Pachan karma of Sunthi and Bilwa, Chardighna Properties of Yava. So here a systematic literature review of Sunthi Bilwa Kwath with Yava Saktu in the management of Garbhini Chardi will be discussed.